Monetary management in Trinidad and Tobago : a chronology, 1964-1994 - Farrell, T.W. ...[et al] (Central Bank of Trinidad and Tobago Port of SpainTT, 1994)
Includes other major developments in the monetary and financial systems of Trinidad and Tobago that have occured since 1989.